Antimicrobial properties of phenolic acid alkyl esters - Eva Feldeková; Michaela Kosová; Markéta Berčíková; Miroslav Dragoun; Iveta Klojdová; Iveta Hrádková; Jan Šmidrkal (Czech Journal of Food Sciences, 2022)
The series of phenolic acid (2-, 3-, 4-monohydroxy- and 2,4-, 2,5-dihydroxy) alkyl esters (methyl, ethyl, propyl, and butyl) were prepared, and their antimicrobial activities were determined. The antimicrobial activity against the tested microorganisms Escherichia coli, Pseudomonas aeruginosa, Staphylococcus aureus, Candida albicans and Aspergillus brasiliensis was investigated and expressed by minimum inhibitory concentration (MIC) in the range of 1.2-20 mM. The inhibitory activity of higher esters of phenolic acids was found to be higher than that of methyl esters and acids. The minimum inhibitory concentration (MIC) of tested compounds was compared with that of 4-hydroxybenzoic acid and its esters (parabens).